CHANGING APPROACHES TO THE STUDY OF INFORMATICS IN THE CONTENT OF TRAINING OF FUTURE ECONOMISTS - Gladchenko, Oksana V. (Educological discourse, 2015)
The problem of changing approaches to the study of informatics by the economists in higher educational establishment, as one of the components of professional competitiveness of future specialists is examined. The feasibility of introduction in the curricula of a number of optional courses aimed at developing skills to work with information in the context of global trends in the information society is proved.